Prolonged neutropenia is a risk of oral adverse events-related sepsis but is not associated with prognosis of tooth extraction in hematopoietic stem cell transplant recipients: A retrospective study. Issue 3 (May 2023) - Shimada, Yasuyuki; Shiko, Yuki; Hangaishi, Akira; Kawasaki, Yohei; Maruoka, Yutaka
Abstract: Background: Although the oral cavity has been identified as a potential site of infection in hematologic malignancies and oral adverse events (OAEs) have been reported to cause life-threatening systemic morbidity, OAEs-related risk factors in hematopoietic stem cell transplantation (HSCT) recipients remain unclear. Purpose: We retrospectively assessed OAEs and risk factors in HSCT recipients in a single center in Japan and discussed the effectiveness of tooth extraction as a method of radically removing dental focal infections (DFIs) prior to HSCT. Results: After exclusions, 99 HSCT recipients (61 men, 38 women) with a median age of 54 (range, 17–69) years at the time of HSCT were identified from a total of 525 patients with hematologic malignancy. Of these, 36 patients (36.4%) experienced OAEs following HSCT, including oral mucositis (n = 29; 80.6%), acute periodontitis (n = 3; 8.3%), oral mucosal edema (n = 3; 8.3%), and oral candidiasis (n = 1; 2.8%). Sepsis derived from OAE was seen in 7 out of 36 (19.4%) patients. None of the tooth extraction cases from our work showed surgical site infections (SSI). A lack of continuous oral evaluation and oral care following HSCT were linked to OAEs (P < 0.05). In addition, as a laboratory factor, a prolonged low absolute neutrophil count (ANC) (<500/μL) resulted in a significantly higher tendency to develop OAE and OAE-related sepsis (P < 0.05). Conclusions: Specialists should continuously monitor the oral health of patients undergoing HSCT. Unpreservable teeth causing dental focal infections should be assessed and extracted prior to HSCT while carefully monitoring the patient's condition following surgery.